2024
DOI: 10.1021/acsomega.4c00723
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Compounds for the Recovery of Critical Elements from Slags: Melt Characteristics of Li5AlO4, LiAlO2, and LiAl5O8

Sven Hampel,
Iyad Alabd Alhafez,
Thomas Schirmer
et al.

Abstract: Engineered artificial minerals (EnAMs) are the core of a new concept of designing scavenger compounds for the recovery of critical elements from slags. It requires a fundamental understanding of solidification from complex oxide melts. Ion diffusivity and viscosity play vital roles in this process. In the melt, phase separations and ion transport give rise to gradients/ increments in composition and, with it, to ion diffusivity, temperature, and viscosity. Due to this complexity, solidification phenomena are y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…If the combustion wasn't fully obtained, about 5 g ammonium nitrate and 10 mL ultra-pure water were added to the cooled beaker followed by another ignition procedure. The total amount of substances was set to 75 mmol requiring two to three ignition steps compared to 25 mmol total amount of substances using only one combustion step [24]. The sol-gel combustion was prepared four times to result in 28.84 g powder.…”
Section: Slag Analogue Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…If the combustion wasn't fully obtained, about 5 g ammonium nitrate and 10 mL ultra-pure water were added to the cooled beaker followed by another ignition procedure. The total amount of substances was set to 75 mmol requiring two to three ignition steps compared to 25 mmol total amount of substances using only one combustion step [24]. The sol-gel combustion was prepared four times to result in 28.84 g powder.…”
Section: Slag Analogue Preparationmentioning
confidence: 99%
“…Starting from the mean square displacement function of the ions at different temperatures the diffusion coefficients of the individual ions in the two phases are calculated. It was previously shown that Li + ions are most mobile [24], this was found here as well in the lithium manganate phase with e.g. diffusion coefficients of 0.45 × 10 −9 m 2 •s −1 at 1700 K and 20.28 × 10 −9 m 2 •s −1 at 2100 K. The manganese cations and the oxygen anions have quite similar diffusion coefficients with 0.7 × 10 −11 m 2 •s −1 for Mn 3+ and 0.3 × 10 −11 m 2 •s −1 for O 2− at 1700 K as well as 3.77 × 10 −9 m 2 •s −1 for Mn 3+ and 4.99 × 10 −9 m 2 •s −1 for O 2− at 2100 K (Figure 11 left).…”
Section: Potential Local Melt Structures and Viscosity By MD Simulationsmentioning
confidence: 99%
See 2 more Smart Citations